Plaque Rupture and Plaque Erosion - Virmani, Renu; Burke, Allen P.; Farb, Andrew (Thrombosis and Haemostasis, 1999)
There are multiple substrates for coronary thrombosis overlying an atherosclerotic plaque. The most common, plaque rupture, consists of an interruption of a thin fibrous cap overlying a lipid rich core. Plaque rupture is a result of macrophage infiltration and matrix degradation, is often seen in calcified plaques, and is highly associated with hypercholesterolemia. A less common substrate, plaque erosion, is not associated with elevated cholesterol and is the prime cause of coronary thrombosis in premenopausal women. The characteristic histologic features are abundant surface smooth muscle cells and proteoglycans, and a small or absent lipid rich core. The mechanisms of plaque erosion are unclear, and there are no consistent risk factors, although patients are often smokers.
Keywords: Coronary atherosclerosis; coronary thrombosis; plaque rupture; risk factors